High potential phytochemical and in vivo anti-inflammatory activity of weedy plants in Sri Lanka: A review - Farzana, M.U.Z.N.; Manuha, M.I.; Nazeem, M.H.M.; Paranagama, P.A. (Faculty of Indigenous Medicine, University of Colombo, 2014)
Anti-inflammatory agent means a substance that counteracts inflammation...
Keywords: HRBC; anti-inflammatory plants; weeds; herbs